2011
DOI: 10.1097/cmr.0b013e328346612c
|View full text |Cite
|
Sign up to set email alerts
|

Beclin-1 and LC3A expression in cutaneous malignant melanomas

Abstract: Autophagy is an intracellular pathway for the degradation of long-lived proteins and damaged organelles. It is, in essence, a recycling process allowing cells to survive oxygen and nutrient depletion. The expression of two autophagy-related proteins, beclin 1 and light chain 3A (LC3A) was investigated in 79 nodular cutaneous melanomas. The results were correlated with histopathological factors, vascular density, and hypoxia-related proteins [hypoxia-inducible factors (HIF1α and HIF2α) and lactate dehydrogenase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 65 publications
3
51
1
Order By: Relevance
“…Moreover, high basal autophagy is required for growth of pancreatic cancer and human cancers carrying activated K-RAS (36,64). Intriguingly, up-regulated autophagy linked to hypoxia and acidity has been reported as a marker of poor prognosis in melanoma and colorectal cancer (39,40). In line with this, autophagy was shown to be mostly localized in hypoxic nonvascularized tumor regions (63), suggesting that autophagy may be important to sustain tumor growth and survival in the developing, scarcely perfused tumors.…”
Section: Discussionsupporting
confidence: 51%
“…Moreover, high basal autophagy is required for growth of pancreatic cancer and human cancers carrying activated K-RAS (36,64). Intriguingly, up-regulated autophagy linked to hypoxia and acidity has been reported as a marker of poor prognosis in melanoma and colorectal cancer (39,40). In line with this, autophagy was shown to be mostly localized in hypoxic nonvascularized tumor regions (63), suggesting that autophagy may be important to sustain tumor growth and survival in the developing, scarcely perfused tumors.…”
Section: Discussionsupporting
confidence: 51%
“…The Beclin-1 gene is located on chromosome 17q21, which is frequently deleted in breast, ovarian and prostate cancer (23). Furthermore, Beclin-1 +/-mutant mice demonstrate a particularly high incidence of tumors, indicating that Beclin-1 may potentially be a haploinsufficient tumor suppressor (24)(25)(26). Thus, in the present study, the expression of Beclin-1 was evaluated in human gastric cancer specimens and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…During the progression of cancer, cancer cells gradually acquire the capacity to evade cell death. Autophagy is an important type of cell death in tumors (23)(24)(25)(26) and Beclin-1 may contribute to its induction. However, although in the early stages, Beclin-1 was strongly expressed in gastric cancer tissues, such changes were not observed in late-stage gastric cancer specimens (TNM stage Ⅲ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that extensive autophagy is generated by tumor hypoxia and anaerobic glycolysis, whereas angiogenesis maintains low autophagic activity. In fact, autophagy localizes to hypoxic regions of tumors most distal to blood vessels where is supports tumor cell survival (Sivridis et al, 2011).…”
Section: Autophagy As a Mechanism For Selective Tumor Growthmentioning
confidence: 99%